A new family of liquid and solid guanidine-based n-type dopants for solution-processed perovskite solar cells. (6th August 2020) - Nakayama, Hidenori; Schneider, Julia A.; Faust, Mina; Wang, Hengbin; Read de Alaniz, Javier; Chabinyc, Michael L.
Abstract : A new family of n-type dopants for organic semiconductors is reported. Changing the alkyl chain of these triazabicyclodecene (TBD) dopants alters their physical properties, including thermal stability, and influences their doping efficiency. Abstract : We present a series of new dopants based on a bicyclcic guanidine-type structure, 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD ), for organic semiconductors. A series of TBD derivatives that were alkylated at the 7-position were synthesized and their physical properties were determined. These stable dopants were shown to be effective n-type dopants for [6, 6]-phenyl- C 61 -butyric acid methyl ester (PC61 BM), poly{[ N, N ′-bis(2-octyldodecyl)naphthalene-1, 4, 5, 8-bis(dicarboximide)-2, 6-diyl]- alt -5, 5′-(2, 2′-bithiophene)} (P(NDI2OD-T2)) and 3, 9-bis(2-methylene-(3-(1, 1-dicyanomethylene)-indanone))-5, 5, 11, 11-tetrakis(4-hexylphenyl)-dithieno[2, 3- d :2′, 3′- d ′]- s -indaceno[1, 2- b :5, 6- b ′]dithiophene (ITIC). Films of PC61 BM doped with 10 mol% of a dimeric derivative of TBD had electrical conductivities of 0.065 S cm −1 . The utility of the dopants was further shown by doping electron transport layers of PC61 BM with 2TBD-C10 for methyl ammonium lead iodide (MAPbI3 ) solar cells leading to improved fill factors and PCEs relative to undoped ETLs.